Molecular identification of Baylisascaris melis (Gedoelst, 1920) from the Eurasian badger (Meles meles) and ascarids from other wild carnivores in Kazakhstan - Uakhit, Rabiga; Smagulova, Ainura; Lider, Lyudmila; Shevtsov, Alexandr; Berber, Alexandr A.; Berber, Alexandr P.; Bauer, Christian; Kiyan, Vladimir (Frontiers in Veterinary Science, 2024)
IntroductionThe presence of gastrointestinal nematodes, including zoonotic ascarids, in wild canids, felids and mustelids as definitive hosts in Central Asian countries has been documented in many studies based on traditional morphological methods. In contrast, relevant data for the badger are scarce. The aim of this study was the molecular identification of ascarid nematodes from five wild carnivore species in different regions of Kazakhstan.MethodsA total of 211 adult ascarids were collected from gray wolves (Canis lupus, 8 of 83 infected with 2–6 Toxascaris leonina), red foxes (Vulpes vulpes, 26 of 53, with 2–8 Toxascaris leonina), corsac foxes (Vulpes corsac, 6 of 11, 3–6 Toxascaris leonina), lynx (Lynx lynx, 2 of 3, with 2–5 Toxocara cati) and badgers (Meles meles, 2 of 4, with 2–7 Baylisascaris melis). Genomic DNA was extracted from the worms and ribosomal DNA, including the first and second internal transcribed spacer genes, was amplified by polymerase chain reaction using specific oligonucleotide primers and then sequenced.ResultsToxascaris leonina, but not Toxocara canis, was molecularly identified in the wild canids, Toxocara cati in the lynx and Baylisascaris melis in the badger. The maximum likelihood phylogenetic tree showed three distinct clades: the canid Toxascaris leonina was placed in one clade, Toxocara cati in another and Baylisascaris melis in a third.DiscussionThe study provides the world’s first molecular data and phylogenetic analysis of Baylisascaris melis, identified for the second time since its description over 100 years ago. This species was shown to be genetically distinct from other Baylisascaris spp. (B. columnaris, B. procyonis, B. transfuga, B. devosi). The possible zoonotic significance of ascarids from wild carnivores is discussed in the light of conditions in Central Asia.